RELATIONSHIP BETWEEN SOCIOECONOMIC STATUS, CORONARY ARTERY CALCIUM AND ATHEROSCLEROTIC CARDIOVASCULAR DISEASE: A MULTI-COHORT STUDY - Taylor Triana, MD, MBA; Mark Berlacher, MD; Karol Watson, MD; Colby Ayers, MS; Elaine Wu, MPH; Shreya Rao, MD, MPH; Tiffany M. Powell-Wiley, MD, MPH; Ambarish Pandey, MD, MSCS; Parag Joshi, MD, MHs; Michael P Bancks, PhD, MPH; Michael Blaha, MD, MPH; Matthew Budoff, MD; et al. (Elsevier, 2023)
Therapeutic Area: ASCVD/CVD Risk Assessment Background: Low socioeconomic status (SES) is associated with atherosclerotic cardiovascular disease (ASCVD) and possible underestimation of risk by pooled cohort equations (PCE). Whether coronary artery calcium (CAC) scores can improve risk discrimination in low SES populations is unknown. Methods: Multi-Ethnic Study of Atherosclerosis (MESA) and Dallas Heart Study (DHS) participants free of ASCVD and with CAC scans were evaluated. Low SES was defined as annual household income <$16,000 (vs. $16-$30,000, >$30,000) or educational attainment <high school (HS) (vs. completed HS, >HS). The relationships between SES, CAC scores (0, 1-99, ≥100), and ASCVD events (fatal/non-fatal MI or stroke) were assessed before/after ASCVD risk factor adjustment (Table). The incremental predictive value of CAC across SES groups was assessed using c-statistics and categorical net reclassification improvement (NRI) (<5%, 5-7.5%, ≥7.5% 10-year ASCVD risk). Results: Among individuals in MESA (n=6164) and DHS (n=2018), SES categories of <$16K, $16-30K, >$30K comprised 19.1%, 18.4%, and 62.5%, and 18.2%, 22.4%, and 59.4% of the study populations, respectively. Individuals with low SES by income (<$16K) had increased ASCVD risk compared to those with higher SES (>$30K) [HRadj 1.38 (95% CI 1.14-1.54) MESA; HRadj 2.52 (1.65-3.85) DHS]. Higher CAC scores were associated with greater 10-year ASCVD risk in each SES category, but the low SES group had the greatest ASCVD risk with CAC=0 (4.9% MESA; 4.3% DHS). CAC scores were independently associated with ASCVD risk among low SES individuals in MESA but not in DHS [CAC>0 vs. 0 HRadj 2.38 (1.64-3.45) MESA; HRadj 1.09 (0.43-2.76) DHS]. Overall, the discriminative ability of CAC for ASCVD was smallest in low SES individuals (c-statistics 0.643 vs. 0.685, 0.711 MESA; 0.680 vs. 0.790, 0.806 DHS) (Table). The addition of CAC to PCE for low SES individuals yielded the smallest incremental improvement in c-statistic and NRI. Defining SES by education yielded similar results. Conclusions: Individuals with low SES have significantly higher ASCVD risk. CAC scores may predict this risk, but have lower ASCVD risk discrimination in this group, and CAC=0 provides less reassurance compared to those at higher SES. These results can assist in determining applications of CAC scanning in those with low SES.